Revision of the genus Luispenaia Martínez (Coleoptera: Scarabaeidae: Melolonthinae: Tanyproctini), with description of three new species from the Atacama Desert, Chile - Mondaca, José; Pizarro-Araya, Jaime; Alfaro, Fermín M. (Zootaxa, 2019)
The genus Luispenaia Martínez (Coleoptera: Scarabaeidae: Melolonthinae: Tanyproctini), is revised and four species are recognized: L. paradoxa Martínez, L. atacamensis new species, L. paposo new species, and L. paulseni new species. This genus is endemic to the Atacama Desert in northern Chile from the regions of Antofagasta to Coquimbo. Diagnostic characters, illustrations, a distribution map, and an identification key are provided for all species. Observations on the habitat, ecology, and distribution of species are given.